2017
DOI: 10.12659/msm.905728
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Predicts the Severity of Incarcerated Groin Hernia

Abstract: BackgroundThe incarceration of a segment of bowel within a groin hernia can result in intestinal strangulation if hernia treatment is delayed. Once intestinal strangulation occurs, a bowel resection may be required, and there is an overall increased risk for postoperative complications. The aim of this study was to identify biomarkers to predict the severity of an incarcerated groin hernia.Material/MethodsWe retrospectively evaluated the records of 95 patients with incarcerated groin hernias who underwent emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 16 publications
1
28
3
Order By: Relevance
“…[ 10 ] Recent studies also generalize the application of NLR to the field of hernia surgery and it was be found to be significantly associated with persistent postsurgical pain bowel, [ 11 ] the presence of a strangulated inguinal hernia, [ 12 ] and bowel resection in incarcerated groin hernia patients. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Recent studies also generalize the application of NLR to the field of hernia surgery and it was be found to be significantly associated with persistent postsurgical pain bowel, [ 11 ] the presence of a strangulated inguinal hernia, [ 12 ] and bowel resection in incarcerated groin hernia patients. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, there are studies showing that there is an increased risk of small bowel resection in patients who are of female gender, [14][15][16] are of advanced age (>65), [14,17] have a long duration of incarceration, [15,[18][19][20] presence of bowel obstruction, [15,18,19] and an apparent peritonitis tableux. [15] Unlike in the studies mentioned above, in this study, it was observed that female gender and older age do not increase the risk of bowel resection.…”
Section: Discussionmentioning
confidence: 99%
“…When we looked at from the perspective of laboratory diagnostic methods, there are studies that assert that increased WBC count, [15,[18][19][20] increased neutrophil count [15,20] and increased NLR ratio, [18] increase the risk of small bowel resection. In all of these studies, comparisons were made according to whether there was a small bowel resection or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil-lymphocyte ratio (NLR) and plateletlymphocyte ratio (PLR) can be a good predictor of the severity of inflammatory response [10][11][12][13]. High NLR and PLR levels can be used as a marker to estimate intestinal necrosis and the need for intestinal resection in patients who will undergo surgery for OH [11,12].…”
Section: Discussionmentioning
confidence: 99%